Publisher Correction: Valproic Acid Sensitizes Hepatocellular Carcinoma Cells to Proton Therapy by Suppressing NRF2 Activation - Jeong Il Yu (Scientific Reports, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.